Deformation behavior of Ti-Zr-Ni-Cu-Be metallic glass and composite in the supercooled liquid region - Bae, DH; Park, JM; Na, JH; Kim, DH; Kim, YC; Lee, JK (CAMBRIDGE UNIV PRESS, 2004)
The deformation behavior of Ti-based bulk metallic glass (BMG) and metallic glass matrix composite (MGMC), both having a multistep crystallization behavior upon heating, has been investigated in the supercooled liquid region. The BMG deforms homogeneously and exhibits moderate elongation to failure due to its multistep crystallization behavior, but shows a significant variation of the flow stress during deformation. For the MGMC containing an in situ beta-phase, a stress-overshoot characteristic, observed in the BMG, is not presented, but elongation to failure is rather limited because the crystalline beta-phase prevents the viscous flow of the amorphous phase. The different presence of the crystalline phases in the metallic glasses can differently affect the flow behavior of metallic glass in the supercooled liquid region.
Keywords: NANOSTRUCTURE-DENDRITE COMPOSITE; ENHANCED PLASTICITY; ALLOYS; PHASE